Efektivitas Media Educaplay Sebagai Game Edukasi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V dalam Pembelajaran Tata Surya - Nadilah, Putri; Hakim, Lukman; Utomo, Budi (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
21st century education requires mastery of various skills, one of which is critical thinking skills. This skill is very important for students in understanding phenomena and solving problems in everyday life, including in science learning. This study aims to determine the effectiveness of Educaplay media as an educational game in improving critical thinking skills of fifth grade students in the solar system material. The research method used is an experiment with a Matching Pretest-Posttest Control Group Design. The research sample consisted of two fifth grade classes at SDN 190 Palembang which were divided into experimental and control classes, each consisting of 23 students. The instrument used was a critical thinking ability test based on the Ennis indicator. Data analysis with normality, homogeneity and t-test tests to determine significant differences between the control class and the experimental class. The results showed that there was a significant difference between the pretest and posttest results in the experimental class using Educaplay media compared to the control class. This proves that the use of Educaplay media is effective in improving students' critical thinking skills. This media is able to present fun, interactive, and challenging learning, thus encouraging students to think analytically and reflectively.